The successful new CEO : the core leadership principles that will guide your first year - Muntean, Christian (Human resource management and organizational behavior collection., 2020)
This book is for anyone on the pointy part of the organizational pyramid, whatever your title is. Every leader and organization is unique. But new CEOs often share many experiences, situations, and decisions. This book shines a light on those and illustrates the fundamental principles that will guide a new CEO through them.